Measuring Peer Group Effects: A Study of Teenage Behavior - Evans, William N.; Oates, Wallace E.; Schwab, Robert M. (Journal of Political Economy, 1992)
Individuals or households often have some scope for choice of peer groups, whether through the selection of neighborhood of residence, school, or friends. This study addresses the estimation of peer group effects in cases in which measures of peer group influence are potentially endogenous variables. Using a rich data set on individual behavior, the paper explores teenage pregnancy and school dropout behavior. For both cases, the estimation of a straight-forward single-equation model yields statistically significant peer group effects; however, these effects disappear under simultaneous equation estimation. The results are robust and suggest the need for careful modeling of the choice of peer groups.